An Environment for Design Space Exploration Using gem5-McPAT - Tashiro, Renan; Oyamada, Marcio Seiji (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2016: Anais do VI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2016)
Design space exploration of embedded systems is an example of a multiobjective problem. At System Level, different solutions can be generated using different mappings of hardware and software. To fulfill the requirements like cost, energy consumption, performance, and power, these different solutions must be evaluated. This work presents an environment for design space exploration aiming to estimate area, energy, performance and power of different solutions in a multicore architecture. To obtain these measures, the simulators gem5 and McPAT are used. They are integrated into the environment VIPEX (Virtual Platform Exploration), a visual framework focused on simplifying the process of design space exploration